2017
DOI: 10.1002/eco.1830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating canopy transpiration and water use of two typical planted tree species in the dryland Loess Plateau of China

Abstract: Large-scale vegetation restoration has been conducted in China's Loess Plateau over the past several decades to control soil and water loss. However, these efforts have not followed any specific guidelines to select plant species that balance the twin goals of vegetation restoration and water demand. In the present study, we measured canopy transpiration characteristics of oriental arborvitae (Platycladus orientalis) and Chinese pine (Pinus tabulaeformis), two species that are commonly planted in restoration e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This facilitative interaction has also been observed among species in plantations even in seasonal drought or semi-arid water limited regions (Wu et al, 2017;Zhang et al, 2017). For example, Zhang et al (2017) suggested the dense canopy cover of P. tabuliformis can reduce the evaporation of soil water in surface layers, which may benefit co-existing species, such as Platycladus orientalis, in the dryland Loess Plateau of China. However, in the semi-arid Loess Plateau of China in the present study, although contrasting physiological adjustments of P. tabuliformis and H. rhamnoides were observed in mixed plantations (Figs.…”
Section: Mixed Afforestation Effects On P Tabuliformis and H Rhamnomentioning
confidence: 83%
See 2 more Smart Citations
“…This facilitative interaction has also been observed among species in plantations even in seasonal drought or semi-arid water limited regions (Wu et al, 2017;Zhang et al, 2017). For example, Zhang et al (2017) suggested the dense canopy cover of P. tabuliformis can reduce the evaporation of soil water in surface layers, which may benefit co-existing species, such as Platycladus orientalis, in the dryland Loess Plateau of China. However, in the semi-arid Loess Plateau of China in the present study, although contrasting physiological adjustments of P. tabuliformis and H. rhamnoides were observed in mixed plantations (Figs.…”
Section: Mixed Afforestation Effects On P Tabuliformis and H Rhamnomentioning
confidence: 83%
“…Co-existing species in natural forest usually exhibit different physiological or morphological adjustments to minimize competition for water during prolonged drought periods (Trubat et al, 2006;Yang et al, 2015). This facilitative interaction has also been observed among species in plantations even in seasonal drought or semi-arid water limited regions (Wu et al, 2017;Zhang et al, 2017). For example, Zhang et al (2017) suggested the dense canopy cover of P. tabuliformis can reduce the evaporation of soil water in surface layers, which may benefit co-existing species, such as Platycladus orientalis, in the dryland Loess Plateau of China.…”
Section: Mixed Afforestation Effects On P Tabuliformis and H Rhamnomentioning
confidence: 95%
See 1 more Smart Citation
“…Franco, a native Chinese Cupressaceae plant, is among the most intensively used cypress species for vegetation restoration projects in northern China (Jiang et al, 2014;. This indigenous species is a perennial evergreen coniferous tree with remarkable longevity that exhibits high tolerance to a diversity of adverse environmental conditions, including drought, freezing temperatures, hot weather, and nutrient imbalances (enrichment and depletion) (Jiang et al, 2014;Wu et al, 2017;Zhang et al, 2017). Other studies have demonstrated that P. orientalis provided considerable ecological benefits for vegetation restoration, especially in fragile ecosystems such as arid and semiarid regions (Yu et al, 2015;Zhang et al, 2017).…”
mentioning
confidence: 99%
“…This indigenous species is a perennial evergreen coniferous tree with remarkable longevity that exhibits high tolerance to a diversity of adverse environmental conditions, including drought, freezing temperatures, hot weather, and nutrient imbalances (enrichment and depletion) (Jiang et al, 2014;Wu et al, 2017;Zhang et al, 2017). Other studies have demonstrated that P. orientalis provided considerable ecological benefits for vegetation restoration, especially in fragile ecosystems such as arid and semiarid regions (Yu et al, 2015;Zhang et al, 2017). However, its survival rate is low due to the poorly developed root systems of container seedlings (Yang et al, 2010;2011) coupled with the extreme environments in which they are transplanted .…”
mentioning
confidence: 99%